An Introduction of a Multi-dimensional Model for Effectiveness of e-commerce in Regulating Market and Pricing of Commodities and Services A Case Study: Selected Guilds of Irans market (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
In this study, we have embarked on identification and studying seminal factors composing e-commerce in Iranian context which has the greatest impact in regulating Iranian market. Factors, studied in this research, are all based on Iranian peoples cultural and societal characteristics, and Iranian markets (selected guilds of computer unions, cell-phone, clothes, and food) features. Reviewing essential strategies in order to regulate Iranian market together with studying e-commerce features illustrates the necessity of determining effective components of e-commerce in regulating Iranian market. This research, in terms of target, is of practical and fundamental type, and, in terms of methodology, is of descriptive kind correlation, and employs a combined method of surveying (face to face and online) and field study. To examine fundamental components of the research a questionnaire was prepared, and the researcher has also used tests of ‘structural equation modelling and track analysis to corroborate the findings of the research. The results of the research showed that e-commerce is effective in regulating market and pricing goods through 5 factors, namely, electronic government, rules and regulations of e-commerce, the culture of using e-commerce, tools of E-Marketing tools and e-commerce technologies, where all factors enjoy enough integrity to compose a sructural equation pattern. Given the use of multi-layer questionnaire and mathematical concepts such as multi-dimensional matrixes, the results, found in research, are introduced as 3-dimential model.